Unmasking “Alekwu” Religious Experience among the Idoma People-Group of Nigeria - Allam, Onmoke Sylvester (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
The phenomenon of “worship” is as old as civilization. The history of “worship” in itself is also the history of the struggle of mankind to attain perfection. From primitive times up to the present, mankind struggled hard to attain perfect knowledge and bliss. The emergence of the spirits and man’s interaction with it is said to be a major way to attain “Bliss” or “self-delight”. This is not possible by the pleasures of the senses. Thus, some religious persons would argue that to attain pure knowledge and bliss, sacrifices and a relationship with spirits is necessary. However, the concepts of ‘spirit’ and ‘spirit worshipping’ remains the most controversial issue within religion and culture. This work attempts to investigate the Idoma concept of “Alekwu” - Ancestors worship. The Idoma people-group is based in modern-day Benue state, in the central part of Nigeria. The Idoma people believe strongly that the spirit of dead ancestors is ever-present within the community. Thus, the concept “Alekwu” indicates the continuous existence of dead ancestors with specific functions. This work is phenomenological in method and has avoided excursions into metaphysics as far as possible. Nevertheless, this work accepts that it positions poses some metaphysical questions and implications.